Material culture, room temperature and the social organisation of thermal energy. (June 2014) - Shove, Elizabeth; Walker, Gordon; Brown, Sam
This article builds on the suggestion that objects should be thought of not as bounded entities but as sites of flow, mixture and mutation. In arguing that processes of thermal exchange are outcomes and expressions of socio-material organization, the authors demonstrate the potential for linking concepts from physics and social science. Drawing on a recent study of air conditioning in the UK, they show that increasingly standardised notions of room temperature have implications for product and building design, and for how energy circulates through the many components and bodies involved. In describing indoor climates in these terms, they develop a social analysis of thermal exchange that is relevant at the molecular level and for long-term trends in energy demand and climate change.